Tuvan-Khakassia marriages and their role in the dynamics of the national composition of the population of Khakassia - Tinikova, Elena E.; Kanzychakova, Nadezhda G. (The New Research of Tuva, 2025)
The article analyzes the impact of migration processes, particularly the migration of Tuvans from Tuva to Khakassia, and the increasing number of interethnic marriages on the dynamics of the ethnic composition of Khakassia’s population. The analysis is based on official statistical data, interviews with experts and individuals in marital unions between Tuvans and Khakassians, as well as those born in such families. The interviews were conducted in two Russian republics in July–August 2024.The 2020 All-Russian Population Census recorded an increase in the number of Tuvans residing in Khakassia. While in 2010 their number was 936 people (0.2% of the total population), by 2020, it had risen to 2,051 people (0.5% of the total population of the republic).Family ties with residents of Khakassia stimulate the relocation of Tuvans to the republic, both among young people, in the context of educational migration, and among middle-aged and older individuals seeking employment in the region. The formation of marital unions between incoming Tuvans and representatives of Khakassia’s titular ethnic group may serve as a factor facilitating their adaptation to the new social environment. In turn, this has a reinforcing effect on their long-term settlement in the republic. In the future, this process may contribute to the further growth of the Tuvan population in Khakassia, significantly influencing its ethnic composition.
Keywords: Tuva; Khakassia; interethnic marriage; national composition; mestizo; Tuvans; Khakassians